2003
DOI: 10.1034/j.1399-3054.2003.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a subtilisin‐like serine protease induced during the senescence of wheat leaves

Abstract: A senescence-specific protease accounting for almost 70% of the total peptide hydrolytic activity of protein extracts, was isolated from detached wheat leaves induced to senescence by incubation in the dark for 72 h. Purification to apparent homogeneity was performed by ammonium sulphate precipitation, ion exchange chromatography and gel filtration chromatography. The enzymatic activity was followed by its ability to hydrolyse the synthetic peptide Suc-AAPF-pNA. SDS/PAGE and gel filtration analysis indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 37 publications
1
29
0
7
Order By: Relevance
“…Cysteine proteinases are also expressed during petal senescence in carnation (Jones et al 1995) and day-lily (Guerrero et al 1998). Although senescenceinduced serine proteases have been identified in wheat leaves (Roberts et al 2003), limited evidence is available for the role of serine proteinases other than the subtilisins (for review, see Beers et al 2000), or their inhibitors, in PCD. Interestingly, subtilisin-like serine proteases are expressed in Arabidopsis vascular bundles, pistils, ovules and anthers (Golldack et al 2003), similar tissues to which SaPIN2a and SaPIN2b have been localized in S. americanum.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine proteinases are also expressed during petal senescence in carnation (Jones et al 1995) and day-lily (Guerrero et al 1998). Although senescenceinduced serine proteases have been identified in wheat leaves (Roberts et al 2003), limited evidence is available for the role of serine proteinases other than the subtilisins (for review, see Beers et al 2000), or their inhibitors, in PCD. Interestingly, subtilisin-like serine proteases are expressed in Arabidopsis vascular bundles, pistils, ovules and anthers (Golldack et al 2003), similar tissues to which SaPIN2a and SaPIN2b have been localized in S. americanum.…”
Section: Discussionmentioning
confidence: 99%
“…Five catalytic classes (serine, cysteine, aspartic, threonine and metallopeptidases) can been identified within the Arabidopsis genome sequence (Rawling et al 2004). In general, proteases are thought to be involved in a range of processes, including germination, senescence, defence responses and programmed cell death (Fontanini and Jones, 2002;Segarra et al 2002;Roberts et al 2003;Coffeen and Wolpert, 2004). In addition, proteases might also play a role in the plant adaptation to changing environmental conditions.…”
mentioning
confidence: 99%
“…Transcriptome study of Arabidopsis senescent leaves also revealed that cysteine and serine proteases are predominantly induced during natural and/or abiotic stress induced senescence (BuchananWollaston et al 2005). Roberts et al (2003) reported a serine protease activity in senescing wheat leaves for which rubisco was a target protein.…”
Section: Discussionmentioning
confidence: 99%